W poszukiwaniu uniwersalnej koncepcji organizmu. Problem indywidualizacji - Stencel, Adrian; Proszewska, Agnieszka (Filozofia Nauki, 2017)
The concept of an organism would seem to occupy a central place in biology, since, ultimately, biology is the science of living organisms. However, despite the undisputed development of biology in recent decades, there is still no universal definition of an organism applicable to different species without raising a number of theoretical problems. One might even get the impression that the opposite is true: that the contemporary life sciences provide us with a multitude of alternative conceptualisations of an organism. In this paper, we try to find a universal concept, one that would establish individuation criteria for organisms as diverse as species of bacteria, humans, and bees. We start by discussing common problems with individuation criteria based primarily on phenotypic characteristics and show why it is difficult to expect this type of definition to pass muster. Next, we present the idea of organismality, which, in our opinion, has the potential to meet this challenge and become the universal concept of an organism.